Clinical outcomes and programming strategies of implantable cardioverter defibrillator (ICD) devices during childhood in hypertrophic cardiomyopathy: a UK national cohort study. (25th November 2020) - Norrish, G; Chubb, H; Field, E; McCleod, K; Till, J; Stuart, G; Hares, D; Linter, K; Bhole, V; Bowes, M; Uzun, O; Sadagopan, S; et al.
Abstract: Background: Sudden cardiac death (SCD) is the most common mode of death in childhood hypertrophic cardiomyopathy (HCM). ICDs have been shown to be effective at terminating malignant ventricular arrhythmias but at the expense of a high incidence of complications. The optimal device and programming strategies to reduce complications in this patient group are unknown. Purpose: To describe the programming strategies and clinical outcomes of ICD implantation in childhood HCM. Methods: Anonymised, non-invasive clinical data were collected from a retrospective, longitudinal multi-centre cohort of children (<16 years) with HCM (n=687) and an ICD in-situ from the United Kingdom. Results: 96 patients (61 male (64%), 6 non-sarcomeric (6%)) underwent ICD implantation at a median age 14yr (IQR 11–16, range 3–16) and weight 52.3 kg (IQR 34.8–63.1). Indication for ICD was primary prevention in 72 (75%). 82 (85%) had an endovascular system, 3 (3%) epicardial and 11 (12%) subcutaneous system. 61 patients (74%) were receiving one or more cardioactive medications at implantation [B blockers n=66, 70%, disopyramide n=14, 15%, amiodarone n=7, 7%, calcium channel blocker n=7, 9%, other n=5, 6%]. Programming practices varied: all had VF therapies activated (median 220bpm, IQR 212–230); 70 (73%) had a VT zone programmed (median rate 187 bpm, SD 20.9), of which 26 (27%) had therapies activated. 50 patients (61%) had antitachycardia pacing (ATP) activated. Over a median follow up of 53.6 months (IQR 27.3, 108.4), 4 patients (4.2%) died following arrhythmic events despite a functioning device. 25 patients had 53 appropriate therapies (ICD shock n=47, ATP n=8), incidence rate 5.22 (95% CI 3.5–7.8). On univariable analysis, secondary prevention indication for ICD implantation was the only predictor of therapy [16 (64%) vs 8 (11.3%), p value <0.001]. 8 (8.3%) patients had 9 inappropriate therapies (ICD shock n=4, ATP n=5), incidence rate 1.37 (95% CI 0.65–2.8), caused by T wave oversensing (n=2), lead migration (n=1), supraventricular tachycardia (n=1). Device complications were seen in 30 patients (31%), including lead complications (n=16) and infection (n=10). No clinical characteristics predicted time to inappropriate therapy or lead complication. Conclusions: In a contemporary cohort of children with HCM, the incidence of inappropriate therapies is lower than previously reported, yet complication rates remain higher than reported in adult patients. No clinical, device or programming strategies were associated with inappropriate therapies or lead complications. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): British Heart Foundation